2016
DOI: 10.3233/wor-162356
|View full text |Cite
|
Sign up to set email alerts
|

Distracting people from sources of discomfort in a simulated aircraft environment

Abstract: BACKGROUND: Comfort is an important factor in the acceptance of transport systems. In 2010 and 2011, the European Commission (EC) put forward its vision for air travel in the year 2050 which envisaged the use of in--flight virtual reality. This paper addressed the EC vision by investigating the effect of virtual environments on comfort. Research has shown that virtual environments can provide entertaining experiences and can be effective distractors from painful experiences. OBJECTIVE: To determine the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…From the in-depth insights of the qualitative reporting, it suggests that food and drink service provides passenger something to do and it distracts them from boredom and the discomfort of lack of leg room. Also VR can distract from a situation with low discomfort [6]. In the retrospective study it is shown that under the same conditions the comfort is rated significantly higher while gaming, walking through the plane, reading, when the garbage is collected, while watching IFE, when listening to music and while the food is being served, probably also because it distracts from the situation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…From the in-depth insights of the qualitative reporting, it suggests that food and drink service provides passenger something to do and it distracts them from boredom and the discomfort of lack of leg room. Also VR can distract from a situation with low discomfort [6]. In the retrospective study it is shown that under the same conditions the comfort is rated significantly higher while gaming, walking through the plane, reading, when the garbage is collected, while watching IFE, when listening to music and while the food is being served, probably also because it distracts from the situation.…”
Section: Discussionmentioning
confidence: 86%
“…Knee space has the highest correlation with comfort [4], which corresponds with the finding of Kremser, Guenzkofer, Sedlmeier, Sabbah and Bengler [5] that seat pitch is an important design factor. Increasing leg room seems to offer the obvious solution to improve comfort, however Lewis, Patel, Cobb, D'Cruz, Bues, Stefano et al showed that by using a VR entertainment system, passengers can be distracted from discomfort caused by a lack of knee space [6]. In addition, Hiemstra-van Mastrigt showed that interaction with other people could also distract from discomfort [7].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual environments can fully or partially distract people from sources of discomfort, becoming more effective when they are interesting. They are also more effective at distracting people from discomfort caused by restricted space than noise disturbances (Lewis et al 2016) MR headsets can also better take into account passenger attitudes towards their environment. For example, Ahmadpour et al (2016) classified these attitudes in terms of: adjusting, avoiding, approaching and shielding, linked to "passengers' concerns for control, privacy, social connectedness and/ or social tolerance".…”
Section: The Benefits Of Mr Headsets: Immersion Limitless Display Spmentioning
confidence: 99%
“…Lewis et al [10] demonstrated that people can be distracted from discomfort caused by the environment, but also showed that the distance between the human and the environment determines the types of senses involved. In the Lewis et al [10], study the eyes played a more dominant role than the close to the body pressure sensors.…”
Section: Future Researchmentioning
confidence: 99%
“…The environment may be close to the human body, i.e., the storage possibilities around the driver or passenger in a car [9] or a virtual reality system distracting the driver from discomfort [10]. The effect of people seated next to each other (neighbors) in an aircraft [11] and variations in posture, which result in more comfort [12], are examples of environments close to the body.…”
Section: Aspects Studiedmentioning
confidence: 99%